Urgensi Sosialisasi Produk Akad Perbankan Syariah terhadap Masyarakat di Kabupaten Bengkalis (Studi Kasus Bank Syariah Mandiri KCP Bengkalis) - Nur Azlina (Akademika: Jurnal Keagamaan dan Pendidikan, 2021)
This study aims to determine the urgency of socialization of the contract of the Syariah Bank Mandiri Branch Office to The Community in Bengkalis Regency. This type of research is a qualitative descriptive approach, namely research that seeks to provide a detailed and in-depth description of the object under study. Data collection techniques from documentation, observation and interviews with the leaders and financing analysts of KCP BSM Bengkalis. From the presentation of the data, it can be concluded that there has been socialization carried out by BSM to provide literacy of the public regarding the presence of sharia banking and contract products applied by BSM to customers through brochures provided by BSM to mosque administrators and educational institutions around Bengalis district.